Thermoluminescent dosimetry in clinical kilovoltage beams - Akpochafor, Michael Onoriode (My University, 2010)
Aim: This study aimed at calibrating a new set of GR-200A thermoluminescent dosimeters (TLDs) in low and medium kilovoltage energy photon therapy beams and in a diagnostic beam of known beam quality, in order to determine their response and to establish if the same set of TLDs could be used across both environments for in-vivo dosimetry purposes. Methods and Materials: A set of 20 TLDs was used for this study. An Oven type PCL3 was used to anneal the TLDs. The response of the TLDs was read using the Reader type LTM manufactured by Harshaw Bicron, United State of America. Vacuum tweezers were used to transfer the TLDs at the time of measurements and calibration. TLDs were kept in a subdued ultra-violet environment between the annealing and irradiation process. TLDs were placed on a 30 x 30 x 17.6 cm³ Polymethylmethacrylate (PMMA) phantom during irradiation. A calibrated Orthovoltage machine was used to deliver a known absorbed dose to the TLDs. A cylindrical ionization chamber (PTW 30001) and an electrometer (PTW 10008) were used to confirm the absorbed dose delivery of the orthovoltage machine at the time of measurement. Likewise, a calibrated LX40 radiotherapy Simulator was used to deliver a known diagnostic absorbed dose to the TLDs. A TM77334 ionization chamber was used similarly to confirm the absorbed dose. The TLDs were also irradiated on the PMMA phantom. The accepted variation in raw response of the individual TLDs from the average of the batch was compared and a deviation of less than ± 20 % was considered within tolerance. A 10 % tolerance was subsequently considered suitable for the measurement of absorbed dose. Results: Of the 20 TLDs calibrated in the 95 kVp therapy beam (3 mm Al half-value layer), 17 were within the accepted response level (i.e. ± 20 % deviation), 17 in the 180 kVp therapy beam (1 mm Cu half-value layer), 16 in the 300 kVp therapy beam (3 mm Cu half-value layer) and 15 in the diagnostic beam of 80 kVp (2.97 mm Al half-value layer). 16 of the 17 TLDs were within ± 10 % dose tolerance at 95 kVp whereas all the TLDs that were within the accepted response level at the 180 kVp and 300 kVp, were within the ± 10 % dose tolerance. 12 of the 15 TLDs at the diagnostic beam energy were within the ± 10 % dose tolerance. Three of the TLDs were therefore rejected at all energies. Conclusion: The study concludes that the same set of GR-200A TLDs could be used across both kilovoltage therapy and diagnostic fluoroscopy environments for in-vivo dosimetry purposes if an accuracy of ± 10 % is considered acceptable, however a separate calibration needs to done at each beam quality. Individual dosimeters from a batch should be carefully identified and sorted during the calibration process prior to clinical use.